Pembelajaran Teknik Dasar Tinju Untuk Atlet Amatir Di Sasana Lion Boxing Academy Kota Malang - Ariyana; Ari Wibowo Kurniawan (Jayabama: Jurnal Peminat Olahraga, 2024)
The process of learning basic boxing techniques at Sasana Lion Boxing Academy requires correct techniques, because observation results show that 87% of amateur athletes at Sasana Lion Boxing Academy Malang City still have not mastered basic boxing techniques. Based on the results of a questionnaire questionnaire for amateur athletes at Sasana Lion Boxing Academy, there are still many who have not mastered basic boxing techniques, such as stance, straight jab, hook, uppurcut and defense. The aim is to develop learning of correct basic boxing techniques for amateur athletes at Sasana Lion Boxing Academy, Malang City. This research uses the Research and Development (R&D) method using the Lee & Owens development model. The subjects tested were 15 athletes. Based on the data obtained based on the results of expert data analysis, namely media experts obtained 80% results, learning experts obtained 89% results, media experts obtained 80% results and field testing results obtained 82%. The results of expert data analysis and field trials obtained "very valid" results. Data collection techniques were carried out through questionnaires and interviews. In conclusion, this learning development product can help amateur athletes at the Lion Boxing Academy Gym, Malang City